Gene expression in the toxic dinoflagellate, alexandrium fundyense emphasis on cell cycle- and growth-regulatory genes - Miranda, Lilibeth N. (Ann Arbor Michigan ProQuest LLC, 2009)
Molecular markers have become an important tool for obtaining in situ growth rates of phytoplankton, which is a key parameter in understanding phytoplankton population dynamics. No molecular markers for in situ growth rate of Alexandrium fundyense are available. In this dissertation, characterization of transcriptional profiles in the cell cycle and identification of potential cell cycle markers for growth studies were done by using a cDNA microarray. A custom cDNA microarray was developed containing 1,512 features to study gene expression at different growth stages and during cell cycle progression. About 2% of the array was differentially expressed between cultures in exponential and stationary phases. By time serial analysis of samples over a 25-h period, 7% of the array was differentially expressed during the cell cycle progression. Three genes (actin, putative "toxin-related" gene and clone 8) exhibited positive correlation in expression levels with the percentage of the cell population in the G2+M stage. This suggests involvement in cell cycle progression and that these genes are potentially useful as cell cycle markers for in situ growth rate studies. Diel transcriptional profiles during a natural bloom of A. fundyense were analyzed by microarray and spliced leader-based cDNA library technique. The diel pattern of the cell cycle progression observed resembled that in the laboratory culture. Microarray analyses showed that 10% of the array was differentially expressed during the light-dark and dark-light transitions, coinciding with the S and G2+M phases of the cell cycle, indicating that the expression of these genes is entrained by these transitions. Some of these genes (DNA damage protein, histone-like protein, and major basic nuclear protein) showed up-regulation only in the G2+M phase, indicative of potentials as cell cycle markers. Consistent with previous studies, results showed that a small fraction of the genome is regulated at the transcriptional level in A. fundyense. The identified genes either previously characterized or novel, are promising candidates for cell cycle markers and need to be further characterized for their applicability to in situ growth rate studies. The putative cell cycle inhibitors also need to be investigated further to gain insights into their roles in cell cycle regulation in this important species.
Thesis (Ph.D.)--University of Connecticut, 2009.
Keywords: Gene expression; Molecular biology